1993
DOI: 10.1080/00405849309543594
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking assessment

Abstract: Resumen Introducción 1. Problema 1.1. Una voz, muchas voces 1.2. Marco 1. Un mundo, los mundos, el globo 1.3. Descripción. 2. Justificación 3. Objetivos 4. Marco referencial 4.1. Estado del arte 4.1.1. De la tragedia cultural a la construcción de una nueva sociedad. 4.1.2. Implicaciones de una investigación desde la complejidad. 4.2. Marco teórico 4.2.1. El hombre orgánico 4.2.1.2. Discusión contemporánea "con" el sur 4.2.1.3. El sistema educativo y su lectura de hombre 4.2.1.4. Desarrollo del humano ecologiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
488
0
141

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 735 publications
(631 citation statements)
references
References 5 publications
2
488
0
141
Order By: Relevance
“…Instruction produces a series of changes in the thinking process that may be difficult to detect with a multiple-choice format. It seems that the best way to evaluate thinking is through open questions, in which students have to justify their point of view (Ennis, 2003). Nevertheless, and for this reason they are less frequently used, such tests are much more costly to correct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instruction produces a series of changes in the thinking process that may be difficult to detect with a multiple-choice format. It seems that the best way to evaluate thinking is through open questions, in which students have to justify their point of view (Ennis, 2003). Nevertheless, and for this reason they are less frequently used, such tests are much more costly to correct.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that our instruments were flawless as regards their psychometric characteristics but were unable to detect the change; that is, they were insensitive to it. In fact, some authors (Ennis, 2003;Govier, 1987) have reported that multiple-choice tests might not be the ideal way to evaluate thinking. Instruction produces a series of changes in the thinking process that may be difficult to detect with a multiple-choice format.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available CT tests use forced-choice item formats. However, it is usually recommended that either a combination of both forced-choice and The tests are aimed at measuring general CT skills and when these items were prepared, the authors used contents from a variety of real world situations that test takers are presumed to be already familiar with constructed-response, or constructed-response items only are used to measure CT skills (Ennis, 1993;Halpern, 2010;Norris, 1989). It is argued that forced-choice items do not directly and efficiently test for significant CT features, such as drawing warranted conclusions, analyzing arguments, and systematically solving problems (Norris, 1989).…”
Section: Methods Planning and Development Of The Ctem Testmentioning
confidence: 99%
“…It is possible to mention the focus of all the other existing domain-general CT tests, and one can reasonably conclude that all the domain-general CT tests are diverse in terms of their formats, scope, and psychometric characteristics. Such variations in CT tests have made the assessment of CT problematic and contentious (Ennis, 1993;Pascarella & Terenzini, 2005). Overall, much of the CT literature associates CT with certain mental processes (such as reasoning, analyzing, predicting, etc.…”
mentioning
confidence: 99%
“…For example, McPeck (1981) considered skills and propensity; Ennis (1989Ennis ( , 1993, abilities and disposition; Facione, Sánchez, Facione and Gainen (1995), skills and disposition. In particular, Facione, Sánchez, Facione and Gainen described the disposition to think critically as "a characterological profile, a constellation of attitudes, a set of intellectual virtues, or ... a group of habits of mind" (p. 1).…”
mentioning
confidence: 99%